DETERMINAN AKUNTABILITAS KINERJA INSTANSI PEMERINTAH (Studi Pada OPD Kabupaten Aceh Tamiang) - Maulia Safrina; Afrah Junita; Nasrul Kahfi Lubis (Program Studi Akuntansi, Fakultas Ekonomi. Universitas Samudra, 2023)
The research was conducted with the aim of knowing the effect of accounting information systems, unethical behavior and compensation on the performance accountability of study government agencies in regional apparatus organizations in Aceh Tamiang Regency. The data used is primary data sourced from research respondents as many as 60 respondents from 30 regional apparatus organizations. Methods of data analysis using quantitative methods with analysis of multiple linear regression equations, test the coefficient of determination (R2) and test the hypothesis (t test and F test). The research results obtained Y = 1.981 + 0.646X1 - 0.366X2 + 0.399X3, a constant of 1.981 is the performance accountability of government agencies before being influenced by accounting information systems, unethical behavior and compensation. The regression coefficient of the variable accounting information system and compensation has a positive effect on the performance accountability of government agencies while unethical behavior has a negative effect on the performance accountability of local government agencies. The test results for the coefficient of determination (R2) of 71.9% accounting information systems, unethical behavior and compensation can explain the performance accountability variables of government agencies, while the remaining 28.1% is influenced by other variables not examined. The results of the partial t test of accounting information systems, unethical behavior and compensation are significant to the performance accountability of government agencies. The results of the simultaneous F test of accounting information systems, unethical behavior and compensation are significant to the performance accountability of government agencies.